PEMBERDAYAAN MASYARAKAT DESA MELALUI PELATIHAN MEKANIK DI KECAMATAN MUARA SATU KOTA LHOKSEUMAWE - Z Zulfahmi; Yasir Amani; Abdul Rahman; Adi Setiawan; Muhammad Nuzan Rizki; A Alchalil (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
Aceh Government data for year 2020 shows the number of vehicles circulating in its territory has reached 2.7 million units of vehicles consisting of 2.1 million motorcycles and 600 thousand cars. Vehicle maintenance and repair service businesses began to grow both in urban and rural areas. The vehicle maintenance and repair service business consist of various areas of expertise including: engine expertise which includes oil changes, engine tune up, engine overhaul, engine electrical and brake systems. While the expertise of the chassis and body (frame and body) which includes: setting the frame, body repair & painting. The achievement of this community service is (1) to provided education and skills regarding service and repair and overhaul techniques for motorcycle components, (2) Provided knowledge about the mechanical working principles of motorcycle components and how to repair them. The training methods used include lectures to increase knowledge on how to repair vehicles; question and answer, discussion, and guidance on motorcycle repair practices. The results of the training, after conducting a basic mechanical competency, participants able to disassemble and reassemble vihicle parts perfectly, and also able to service and perform vehicle maintenance proficiently.